Negotiation communication revisited - Mareike Schoop (Central European Journal of Operations Research, 2021)
Negotiators communicate with each other and decide on offers or requests. Whilst the decision side of negotiations has long been a focus of negotiation research, the communication side has not been extensively supported. The current paper revisits the need for a communication perspective in business negotiations and reviews current research on negotiation communication. Both strands of relevant work are then integrated to provide a concept of electronic negotiation communication and to discuss how this concept was implemented in the system Negoisst and thus operationalised.
Keywords: 650; Negotiation communication; Electronic negotiation; Language–action perspective; Negoisst